Exercise Fails to Improve Neurocognition in Depressed Middle-Aged and Older Adults - Hoffman, Benson M.; Blumenthal, James A.; Babyak, Michael A.; Smith, Patrick J.; Rogers, Sharon D.; Doraiswamy, P. Murali; Sherwood, Andrew (East Carolina University, 2008)
Purpose: Although cross-sectional studies have demonstrated an association between higher levels of aerobic fitness and improved neurocognitive function, there have been relatively few interventional studies investigating this relationship, and results have been inconsistent. We assessed the effects of aerobic exercise on neurocognitive function in a randomized controlled trial of patients with major depressive disorder (MDD). Methods: Two-hundred and two sedentary men (n = 49) and women (n = 153), aged 40 yr and over and who met diagnostic criteria for MDD, were randomly assigned to the following: a) supervised exercise, b) home-based exercise, c) sertraline, or d) placebo pill. Before and after 4 months of treatment, participants completed measures of: Executive Function (Trail Making Test BA difference score, Stroop Color/Word, Ruff 2 & 7 Test, Digit Symbol), Verbal Memory (Logical Memory, Verbal Paired Associates), and Verbal Fluency/Working Memory (Animal Naming, Controlled Oral Word Association Test, Digit Span). Multivariate analyses of covariance were performed to test the effects of treatment on posttreatment neuropsychological test scores, with baseline neuropsychological test scores, age, education, and change in depression scores entered as covariates. Results: The performance of exercise participants was no better than participants receiving placebo across all neuropsychological tests. Exercise participants performed better than participants receiving sertraline on tests of executive function but not on tests of verbal memory or verbal fluency/ working memory. Conclusions: We found little evidence to support the benefits of an aerobic exercise intervention on neurocognitive performance in patients with MDD. Originally published Medicine and Science in Sport and Exercise, Vol. 40, No. 7, July 2008
Keywords: Fitness; Depression; Cognitive functions; Executive functions